PERANCANGAN CORPORATE IDENTITY CV ROBI TEKNIK KONSTRUKSI DI PADANG - FAIZAL RAEFAHUWA, Ishakawi, S.Pd, M.Ds, Eliya Pebriyeni, S.Pd, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
In the design og logos, displayed information about the company as well as several alternativ designs, and supporting appropriate and elementsof design such as line, color, typography, shape, size, texture, value and the use of other fonts and logo to be final. He designed the company logo as a supporting media identity as an additional promotion, the company is expected to be the identity in additional to the interaction of identity is also more robust and blossoms grow in a healthy interaction and competitive. Keywords : logos, the company logo and corporate identity